Potencjał konkurencyjny podkarpackich producentów żywca wieprzowego na tle producentów krajowych - Kilar, Janusz; Kusz, Dariusz; Stec, Artur (Competitive Potential of the Porker Producers from the Podkarpacie Region Against the Background of National Producers, 2006)
It has been found that the headage of pigs in the province of Podkarpacie is characterised by significant lack of concentration. Farms with small herds of pigs prevail, which negatively influences their market position and the economic results achieved. A chance for porker production on a smaller scale lies in the horisontal integration of farmers through getting organised into producer groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 413-418